Wassily Leontief and input-output economics - Leontief, Wassily W. 1906-1999; Dietzenbacher, Erik 1958-; Lahr, Michael L. (Cambridge University Press, 2004)
Wassily Leontief (1905–1999) was the founding father of input-output economics, for which he received the Nobel Prize in 1973. This book offers a collection of papers in memory of Leontief by his students and close colleagues. The first part, 'Reflections on Input-Output Economics', focuses upon Leontief as a person and scholar as well as his personal contributions to economics. It includes contributions by Nobel Laureate Paul A. Samuelson who shares his memories of a young Professor Leontief at Harvard and ends with the last joint interview with Wassily and his wife, to date previously unpublished. The second part, 'Perspectives of Input-Output Economics', includes theoretical and empirical research inspired by Leontief's work and offers a wide-ranging sample of the state of interindustry economics, a field Leontief founded. This is a strong collection likely to appeal to a wide range of professionals in universities, government, industry and international organizations
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Leontief, Wassily / 1906-1999; Leontief, Wassily W. -- 1906-1999; Geschichte 1900-2000; Geschichte; Mathematisches Modell; Wirtschaft; Economics / United States / History / 20th century; Economists / United States / Biography; Economics, Mathematical / History; Business cycles / Mathematical models / History; Input-output analysis; Input-Output-Analyse; USA; Biografie